Future changes in the ecosystem services at Guanacaste Conservation Area, Costa Rica and their implications for the nearby communities of the Central American Dry Corridor - Alfaro Martínez, Eric J. (2022)
We present a valuation of the main ecosystem services of the Rincon de la Vieja National Park (RVNP), as part of the Guanacaste Conservation Area (GCA) in the North Pacific of Costa Rica. The analysis consisted of an approximate valuation of their existence for society, employing a method called Chain Cluster and Unit Value Transference (Moreno et al., 2019). Moreover, data from General Circulation Climate Models were used to analyze precipitation and temperature variations from 1979 to 2099, and to explore a possible impact in these ecosystem services in the future (Hidalgo and Alfaro, 2017; Hidalgo et al., 2021). As an example, results showed that for 2017, the activities around RVNP generated around US$95.7 million. Analysis of the climate model output showed that on average, temperature would present future warming trends and drier precipitation conditions in Guanacaste. Temperature trends are monotonic, while precipitation trends tend to be aggravated in the second half of the century. This means that the ecosystem services could be reduced in the future, because of an increase in the aridity. These changes could affect mainly the communities located nearby the National Parks of the GCA belonging to the Central American Dry Corridor. This Dry Corridor is a mainly rural area characterized by a marked precipitation seasonality, climate change vulnerability, rich biodiversity, entrenched poverty, food insecurity, and outmigration. The main service that would be affected is water supply for human consumption generating a conflict between this service and conservation.